Darul Ahdi wa Syahadah and the Implementation of Maqasid Al-Shariah in the Context of the Pancasila State - Saputra, Edy; Ridwan, Mohammad; Effendi, Amri; Rita Defriza; Hidayat, Rahmad (Nurani, 2024)
This research explores the application of the concept of Darul Ahdi Wa Syahadah as a foundation for implementing Maqasid al-Shariah within the context of the Pancasila state. The aim is to examine how Islamic values, which protect religion, life, intellect, progeny, and property, align with the principles of pluralism and diversity enshrined in Pancasila, ultimately striving to achieve a just, prosperous, and harmonious Indonesian society. Using a qualitative approach with a literature review and critical discourse analysis, this study examines various scientific works, official Muhammadiyah documents, and public policy reports. Findings reveal that Darul Ahdi wa Syahadah and Maqasid al-Shariah can harmonize in public policies that promote social justice and welfare in alignment with Pancasila’s principles, underscoring the role of Muhammadiyah as a key agent in integrating Islamic values with state ideology. Despite significant challenges, particularly concerning pluralism and religious freedom, these concepts hold substantial potential to reinforce social and political stability in Indonesia. Future research should focus on developing specific indicators to assess the effectiveness of Darul Ahdi wa Syahadah and Maqasid al-Shariah in public policies across sectors such as education, economic development, and healthcare. Additionally, empirical studies should be conducted to evaluate the broader societal reception of these concepts within Indonesia's pluralistic framework.